Peranan Lembaga Penunjang Terhadap Pengembangan Agribisnis Stroberi Di Kabupaten Bolaang Mongondow Timur - Mambu, Patricia Like; Loho, Agnes Estephina; Sendow, Martha Mareyke (Sam Ratulangi University, 2023)
This study aims to determine the supporting institutions for strawberry agribusiness, and the role of supporting institutions in the development of strawberry agribusiness in Mooat Village and South Bongkudai Village, East Bolaang Mongondow Regency. This research was conducted from May to August 2022. This research method uses a survey method. The research locations are all areas that grow strawberries. The data used in this study are primary data and secondary data. Primary data were obtained from respondents, namely farmers and institutions that support the development of strawberry agribusiness, namely agribusiness supporting institutions. Secondary data was obtained from the government, sub-district office, mooat village office, and literature studies. The sampling method used is multistage random sampling. Data analysis used in this research is descriptive analysis. The results showed that agribusiness supporting institutions in East Bolaang Mongondow Regency included Bank BRI, Bank SulutGo, BNI, and BPR, Savings and Loans Cooperatives, Producers Cooperatives, Consumer Cooperatives, Service Cooperatives, Multi-Business Cooperatives. Research and Technology Institutions in the form of Agricultural Vocational Schools, and Universities. Fisheries and Forestry Extension Center (F2EC), Production Facilities Agency.